Bone marrow transplantation for mucopolysaccharidosis type I: experience of two British centres. Issue 2 (1st February 1997) - Vellodi, A; Young, E P; Cooper, A; Wraith, J E; Winchester, B; Meaney, C; Ramaswami, U; Will, A
Abstract : Bone marrow transplantation was carried out on 38 patients with mucopolysaccharidosis type I over a period of 15 years. The donor was an HLA identical relative in 10 cases, an HLA non-identical relative in 16 cases, and an HLA identical unrelated volunteer donor in 12 cases. Ten patients received a second transplant. One patient received three transplants. Thirteen engrafted patients have survived five years or more. Most patients have shown an arrest or slowing down of psychomotor regression. However, dysostosis multiplex has progressed. Careful selection of patients may be necessary to ensure optimum results.